Primary Pupils' Multimodal Representations in Worksheets-Text Work in Science Education - Fredrik Jeppsson; Kristina Danielsson; Ewa Bergh Nestlog; Kok-Sing Tang (MDPI AG, 2022)
Worksheets are common in science classrooms with an aim to support pupils' meaning-making, e.g., for guiding them in performing hands-on activities and documenting their experiences of such activities. Yet, there have been few systematic studies of pupils' disciplinary representations in worksheets. Drawing on systemic functional linguistics, we have analyzed fifth grade pupils' (age 10-11) multimodal texts in worksheets (n = 25) when they were working with shadow formation as part of their regular classroom activities. In the worksheets they were asked to first explain in writing why or why not a shadow was formed and then explain shadow formation through a drawing. At an overall level, we found that a majority of the pupils managed to express in writing why a shadow is formed, though it appeared to be more challenging for them to explain why a shadow is not formed. In their drawings, quite a few pupils managed to include several key aspects of shadow formation, at least when combining image with writing. For all tasks, the explanatory parts of the pupils' responses were often implicit. Based on our results, we suggest that pupils may benefit from teaching practices that integrate a parallel focus on form and content as a way to raise their awareness of, for instance, the affordances of different resources and how explanations can be structured. Such practices may support pupils to be able to consider and choose appropriate resources in their disciplinary texts.